Influence of iodine supplementation on serum insulin-like growth factor-I (IGF-I) and IGF-binding protein-3 (IGFBP-3) levels in severe iodine deficiency - Özön, Alev; Alikaşifoğlu, Ayfer; Yordam, Nurşen (The Turkish Journal of Pediatrics, 2004)
Iodine deficiency is an important public health problem worldwide. In addition to severe consequences such as brain damage, developmental delay, deficits in hearing and learning, it also has a negative impact on growth. The negative impact of severe iodine deficiency (SID) on insulin-like growth factor-I (IGF-I) and insulin-like growth factor binding protein-3 (IGFBP-3) was shown previously. In this study we aimed to analyze the impact of iodine supplementation on growth and growth factors of children with SID. One hundred and four children (63 boys and 41 girls) aged 5-15 years participated in the study. Height standard deviation scores (HSDS), and serum levels of IGF-I and IGFBP-3 were assessed both before and six months after a single dose of iodized oil. Serum levels of free thyroxine (FT4) and thyroid stimulating hormone (TSH) were also analysed to investigate the mechanisms by which alterations of iodine status may influence growth. Pubertal children had lower HSDS six months after iodine supplementation, while that of prepubertal children remained unchanged. IGF-I and IGFBP-3 levels decreased significantly and FT4 levels were suppressed six months after the supplementation, while TSH was normalized. These findings suggest a negative impact of iodine supplementation on growth factors in the short-term, which may be a direct effect of iodine repletion or an indirect effect caused by alterations in thyroid function. It may also be related to the method of supplementation used. Further studies are necessary to resolve these issues, as well as to examine the impact of iodine supplementation on growth in the long-term.